"Teste di mazza": The Nuragic Mace-Heads (Sardinia, Italy). Technological and Experimental Analysis. (2nd April 2020) - Martellotta, Eva Francesca; Castangia, Giandaniele; Lemorini, Cristina
ABSTRACT: We present the results of a study on the experimental reproduction of a specific type of macro-lithic tool, traditionally called "teste di mazza", distinctive to the Nuragic phase in Sardinia (17th-9th century BC). We analyzed a sample collected in the area of northern Sinis – in the western-central part of the island – in order to reconstruct the sequence of the technological actions required to produce these tools. At this point, two experimental copies were manufactured, documenting the process and especially the macro-traces left on the surface of the instruments which were used to make comparisons with the archaeological data.